Joyful Learning as a Worthwhile Instructional Activity for English Beginner Students in the Post Covid 19 Pandemic Era - Maming, Khadijah; Patahuddin; A, Nasrullah; Sianna; Arsyad, Nur Ainun (Ethical Lingua: Journal of Language Teaching and Literature, 2023)
During the Covid-19 pandemic, there were many ways that schools used to keep learning going, and one of the learning approaches that are meaningful and fun in the child's world is joyful Learning. SDIT Al-Furqan located in Enrekang regency, South Sulawesi, Indonesia, also felt the impact of the Covid-19 pandemic. The most visible effect is that their enthusiasm for Learning has decreased because they have been "sent home" for a long time. The researchers concluded that using children's songs will be easy to gain success in their listening goal and make the students more interested in learning English. For this reason, English for beginners in the new normal era through joyful Learning can be used as a choice to restore the learning mood of students. Joyful Learning assumed as a worthwhile learning activity in English. The researcher applied a pre-experimental class design with one group pretest and posttest design. The population of this research was fifth-grade students of SDIT AL-Furqan, Indonesia. The data analysis showed that the joyful learning method positively impacts the students. It was proved by the students' mean score in pretest was better than in posttest. Moreover, the students also give their positive perceptions of implementing joyful Learning. Briefly, joyful learning activities positively affect beginner elementary school students' English achievement.